Implementation of the Principle of Common Heritage of Mankind According to the UN Convention on the Law of the Sea of 1982 - Sitompul, Mhd. Nasir (International Asia Of Law and Money Laundering (IAML), 2024)
Common Heritage of Mankind is a principle in the International Law of the Sea system where the principle provides freedom of Natural Resources contained in the International Seabed or Seabed Area. The regulation of international law authorizes an international organization called the International Seabed Authority to carry out its role as supervision of the implementation of the principles of Common Heritage of Mankind in the International Seabed area. Article 136 of the International Convention on the Law of the Sea, Part XI of the Area states that “ the area and its resources are the common heritage of mankind”. In applying the principles of the Common Heritage of Mankind contained in Chapter XI UNCLOS 1982 was implemented under the Implementation Agreement 1994 which then established an international organization authorized to fully regulate and manage the resources that exist in the seabed and Deep Ocean where the common heritage of mankind on behalf of it acts.